Frequency of French-American-British subtypes of acute myeloid leukaemia in a tertiary care hospital of Karachi - Bhatti, Irtiza Ahmed; Haider, Ghulam; Khan, Youksal Intikhab; Saifuddin, Taher (Journal of the Pakistan Medical Association, 2022)
The aim of this study was to determine the frequency of different subtypes of acute myeloid leukaemia (AML) cases that presented in a tertiary care hospital of Karachi. It was a retrospective cross-sectional study, conducted in the hospital’s Oncology department. Data of patients admitted during 2018 was collected from the records. In this study, patients were included using the non-probable convenient sampling technique. Selected cases were classified according to the French-American-British (FAB) classification and data analysis was performed using the SPSS version 25.0. Among the 61 patients included in the study, 28 were males and 33 were females, with a male to female ratio of 1:1.2. The patients’ age ranged between 15 and 92 years and the mean age of diagnosis was 36.13± 15.5 years. M2 was the most common FAB subtype in 14(29.8%) patients, followed by M1 in 11(23.4%) patients. Myeloperoxidase (MPO) was positive in 44 (71.4%) of those cases. Keywords: Acute myeloid Leukaemia (AML), French-American-British (FAB) classification.